Kemampuan Guru Biologi Kelas XI dalam Penerapan Kurikulum 2013 di SMA Negeri se-Kabupaten Pekalongan Semester Genap Tahun Ajaran 2014/2015 - SYAIFULLAH, Achmad; , Dra. Hariyatmi, M.Si (2015)
The ability of teachers to implement the curriculum implementation in 2013 include at least three things: the ability to plan the implementation of learning, the ability to carry out learnipng activities and assessment capabilities of teachers in implementing the learning process. This study aims to determine the ability of a biology teacher in eleven grade High School in Pekalongan district in the implementation of the curriculum 2013 school year 2014/2015. This research is a qualitative description using a case study approach. Data collection techniques using documentation and observation. The results obtained are: (1) The ability of teachers in High School biology eleventh grade in Pekalongan district in preparing lesson plan based on the curriculum 2013 school year 2014/2015 amounted to 67.15% (B), Riduwan, 2010. (2) The ability of teachers in High School biology eleventh grade in Pekalongan district in implementing learning activities based curriculum 2013 school year 2014/2015 was 76.38% (SB), Riduwan, 2010. (3) The ability of teachers in High School biology eleventh grade in Pekalongan district in carrying out the assessment of learners based curriculum 2013 school year 2014/2015 amounted to 53.69% (B), Riduwan, 2010.